Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Para resolver el problema, debemos seguir los pasos específicos para evaluar y comparar los valores de la función [tex]\( f(x) \)[/tex]. La función dada es [tex]\( f(x) = 2x^2 + 3x + 6 \)[/tex]. Vamos a calcular los valores de [tex]\( f(2) \)[/tex] y [tex]\( f(-3) \)[/tex], y luego encontrar la diferencia [tex]\( f(2) - f(-3) \)[/tex].
### Paso 1: Calcular [tex]\( f(2) \)[/tex]
Primero, sustituimos [tex]\( x = 2 \)[/tex] en la función [tex]\( f(x) \)[/tex]:
[tex]\[ f(2) = 2(2)^2 + 3(2) + 6 \][/tex]
Calculamos los términos uno a uno:
[tex]\[ (2)^2 = 4 \][/tex]
[tex]\[ 2 \cdot 4 = 8 \][/tex]
[tex]\[ 3(2) = 6 \][/tex]
Entonces:
[tex]\[ f(2) = 8 + 6 + 6 = 20 \][/tex]
### Paso 2: Calcular [tex]\( f(-3) \)[/tex]
Ahora, sustituimos [tex]\( x = -3 \)[/tex] en la función [tex]\( f(x) \)[/tex]:
[tex]\[ f(-3) = 2(-3)^2 + 3(-3) + 6 \][/tex]
Calculamos los términos uno a uno:
[tex]\[ (-3)^2 = 9 \][/tex]
[tex]\[ 2 \cdot 9 = 18 \][/tex]
[tex]\[ 3(-3) = -9 \][/tex]
Entonces:
[tex]\[ f(-3) = 18 - 9 + 6 = 15 \][/tex]
### Paso 3: Calcular [tex]\( f(2) - f(-3) \)[/tex]
Finalmente, encontramos la diferencia entre [tex]\( f(2) \)[/tex] y [tex]\( f(-3) \)[/tex]:
[tex]\[ f(2) - f(-3) = 20 - 15 = 5 \][/tex]
### Conclusión
El valor de [tex]\( f(2) - f(-3) \)[/tex] es [tex]\( 5 \)[/tex]. Por lo tanto, la respuesta correcta es:
C) 5
### Paso 1: Calcular [tex]\( f(2) \)[/tex]
Primero, sustituimos [tex]\( x = 2 \)[/tex] en la función [tex]\( f(x) \)[/tex]:
[tex]\[ f(2) = 2(2)^2 + 3(2) + 6 \][/tex]
Calculamos los términos uno a uno:
[tex]\[ (2)^2 = 4 \][/tex]
[tex]\[ 2 \cdot 4 = 8 \][/tex]
[tex]\[ 3(2) = 6 \][/tex]
Entonces:
[tex]\[ f(2) = 8 + 6 + 6 = 20 \][/tex]
### Paso 2: Calcular [tex]\( f(-3) \)[/tex]
Ahora, sustituimos [tex]\( x = -3 \)[/tex] en la función [tex]\( f(x) \)[/tex]:
[tex]\[ f(-3) = 2(-3)^2 + 3(-3) + 6 \][/tex]
Calculamos los términos uno a uno:
[tex]\[ (-3)^2 = 9 \][/tex]
[tex]\[ 2 \cdot 9 = 18 \][/tex]
[tex]\[ 3(-3) = -9 \][/tex]
Entonces:
[tex]\[ f(-3) = 18 - 9 + 6 = 15 \][/tex]
### Paso 3: Calcular [tex]\( f(2) - f(-3) \)[/tex]
Finalmente, encontramos la diferencia entre [tex]\( f(2) \)[/tex] y [tex]\( f(-3) \)[/tex]:
[tex]\[ f(2) - f(-3) = 20 - 15 = 5 \][/tex]
### Conclusión
El valor de [tex]\( f(2) - f(-3) \)[/tex] es [tex]\( 5 \)[/tex]. Por lo tanto, la respuesta correcta es:
C) 5
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.